ASSESSMENT OF TRIMETHOPRIM -LOAD SOLD LIPID NANOPARTICLES ACTIVITY AGAINST STAPH AUROUS ISOLATED FROM URINARY TRACT INFECTIONS IN WOMEN (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Objective: to Isolate Staph aurous from urinary tract infection in women and study in the vitro antibiotic of the standard Trimethoprim and Trimethoprim loaded solid lipid nanoparticles formulation against Staph aurous isolated. Method: A total of 123 urine samples from women patients with urinary tract infections were gathered, from different hospitals around waist province from 15 June for 15 September, 2023. Morphological characteristics and biochemical tests based on Api20, Vitek 2 system, and Bogy's Manual of Systematic Bacteriology were used to identify the samples Result: The results were 60 (48.7%) isolates of Staph aurous obtained from 123 from women with urinary tract infections (UTI), distributed as symptomatic 71(57.7%) and asymptomatic 52 (42.3%). In-vitro Antibacterial Activity the activity of TMP-SLNs formulation and standard TMP against UTI isolates of Staph aurous was sensitive to the tested formulations. The TMP-SLNs formulation shown considerably greater (p